2022-RA-943-ESGO The significance of lower uterine segment involvement in endometrial cancer. (20th October 2022) - Davidesko, Sharon; Meirovitz, Mihai; Brami, Hagar; Shaco-Levy, Ruthy; Meir, Amit; Rabinovich, Alexander; Kezerle, Yarden; Benzion, Samueli; Yarza, Shaked; Kessous, Roy
Abstract : Introduction/Background: Limited data suggests that lower uterine segment (LUS) involvement may be associated with other poor prognostic factors such as lymphovascular space involvement (LVSI), deep myometrial invasion and high-grade histology, but its impact on disease progression is unclear. This study assesses the impact of LUS involvement on the prognosis of women with endometrial cancer. Methodology: A revision of all pathological samples following surgical staging for endometrial cancer between the years 2002 to 2022 was performed and retrospective clinical data collected from patients' medical records. Characteristics of women with and without LUS involvement were compared and outcomes of both groups analysed. Kaplan Meyer survival curves were constructed comparing overall survival (OS) and progression-free survival (PFS) in both groups. Results: 429 women were included in the study, 45 (10.5%) were diagnosed with LUS involvement. No differences were found between the groups regarding the demographic or clinical characteristics including age, hypertension, diabetes mellitus, smoking, obesity, infertility, hormonal therapy or histological subtype. LUS involvement was significantly associated with LVSI (40% vs. 22% p=0.01), higher stage at diagnosis (p=0.04), and shorter PFS (30.0 months vs. 55.2 months, p=0.02). A decrease in 5 year OS was also observed although this marginally missed statistical significance (88% vs. 77%, p=0.06). A trend towards decreased PFS and OS was demonstrated in the Kaplan Meyer survival curves, however these failed to reach statistical significance, possibly due to an insufficient number of cases ( figure 1 ). Conclusion: LUS involvement appears to confer a poorer prognosis with decreased PFS and a trend towards decreased OS and may be an additional factor to consider in decisions regarding adjuvant treatment following surgical staging for endometrial cancer.